Jung e a narrativa: mito individual e inconsciente coletivo - Arantes, Ana Cláudia Yamashiro (Universidade Federal de São Carlos, 2006)
This work intends to offer a different reading of Carl Gustav Jung writings of the ones that conceive the terms archetype and collective unconscious as explicit references to the transcendent domain, "spiritualistic" readings that would do the Analytical Psychology methodology result in a dogmatic proceeding. In order to understand the notion of "individual" that has place in the Jungian meta-psychology , it becomes important to understand Jung's way to mean and to interpret the psychopathological facts and dreams that him observed in his clinical experience. Every moment the analytical psychology threatens to relapse in an irrationalism if we restrict ourselves in the denotative consideration of the language used to represent the psychic reality. We put emphasis, in our reading, on the representative and symbolic use of the language of psychological communication that intends to express the individual being, in order to investigate the question of the dogmatism that permeates countless critical readings concerning Jung's work. After all, in which paradigm the Analytical Psychology intends to sustain itself as a science? We will show that is the material-reductionism paradigm from the sciences of the nature the responsible for guiding the comprehension of a (transcendent) origin of the collective unconscious archetypes, but these are only enunciated by Jung in order to refer to the (figurative) appearance of the dreamlike fantasies for the psychic (immanent) existence. The causal factor stops being predominant in the interpretation of the archetype concept to give up place to the adaptation purpose of the psychic manifestation of the image. The notion of normality is faced, and crosses the domains of the disease in which takes place the eighty century medicine; if this natural paradigm becomes unable to guide the analytical psychology point of view, that intends to be a science of the man, which new paradigm would be more appropriated in a reading of Jung's work that do not intends to aim in a dogmatic interpretation - what would invalidate it's scientific legitimacy? To understand the pretense connection of the Jungian work to the mystic's domain it is necessary to understand the notion that the history of the philosophical thought checked to the term "dogmatism ". At last, could the Analytical Psychology be understood as a Science, or does it approach more to the Art, that intends to turn the part (finite) the representation of the essence of the "whole" (infinite)?
Keywords: Filosofia - história; Dogmatismo; Religiosidade; Simbolismo; Subjetividade; Dogmatism; Psychologism; Religiosity; Symbolic language; Psychic causality; Subjectivity; CIENCIAS HUMANAS::FILOSOFIA